METTL3 Is Involved in the Development of Graves’ Disease by Inducing SOCS mRNA m6A Modification - Song, Rong-hua; Du, Peng; Gao, Chao-qun; Liu, Xue-rong; Zhang, Jin-an (Frontiers in Endocrinology, 2021)
Objective Epigenetic modifications in RNA are known to play critical roles in cell differentiation through regulating expressions of some key genes including members of the suppressor of cytokine signaling (SOCS) family. The present study aimed to unveil the relationship of SOCS mRNA methylation induced by methyltransferase like 3 (METTL3) with Graves’ disease (GD). Methods Differently expressed genes (DEG) in GD tissues were identified using microarray analysis and further validated using CD4+ T cell microarray of GD tissues and isolated peripheral blood mononuclear cells (PBMCs). Furthermore, expressions of METTL3 targeted genes were detected using METTL3 knock-down experiment in RAW264.7 cells. Results High throughput microarrays revealed that METTL3 and SOCS molecules were aberrantly expressed in thyroid tissues and CD4+T cells of GD compared to the controls. Bioinformatic analysis was undertaken by searching databases of found genes of the SOCS family that possessed many mRNA m6A modification loci. METTL3 knock-down experiment revealed that expressions of SOCS family members SOCS1, SOCS2, SOCS4, SOCS5, and SOCS6 were increased after METTL3 knock-down. Conclusions For the first time, the present study revealed the relationship between m6A modification and GD and indicated that METTL3 may be involved in the development of GD by inducing mRNA m6A methylation modification of SOCS family members.